Prevalence of endoparasitic fauna of various species of birds in North-Eastern region of India. Issue 6 (3rd July 2021) - Patra, Gautam; Efimova, M. A.; Sahara, Ana; Al- Abodi, Hiba; Borthakur, Sonjoy; Ghosh, Subhamoy; Polley, Shamik; Debbarma, Apurba
ABSTRACT: The prevalence of endoparasitic infections of birds in different zoological gardens in North-Eastern region of India was investigated from February 2018 to January 2019. Coprological examination included 1, 275 faecal samples from 10 different species of captive birds in six zoo gardens. The prevalence of blood parasites was also carried out by examining a total of 175 blood samples. Faecal samples were examined by flotation method using saturated salt solution and also by conventional sedimentation method. The blood was examined after staining with Giemsa stain. The overall prevalence of helminths was 29.25%. We have found coccidian oocysts, eggs of Capillaria spp, Ascaridia spp, Heterakis spp, Raillietina tetragona, R. cesticillus, Echinostoma spp, Strongyloides avium, Dispharynx spp and eggs of unidentified trematode. Co-infections with more than one species were recorded from some Zoological gardens. Among all the blood samples examined 11.5% were found infected with Haemoproteus spp and 6.25% with Plasmodium spp. No mixed infection with blood parasite was observed in the present investigation. The results found can be implicated for healthcare protection of endangered bird species from this region of India.